2015
DOI: 10.1080/08946566.2015.1094300
|View full text |Cite
|
Sign up to set email alerts
|

Financial Abuse of Older Women in Serbia

Abstract: A survey of older women in Serbia was conducted to understand the structural and individual financial abuse they experienced within the family context, as well as the risks of this form of abuse and their knowledge of their rights. This is the first study on financial abuse of older women in Serbia. It has important implications for older women who experience lower overall economic status than older men and women of younger ages. A convenience sample of 97 older women age 65 years and older from ten cities/mun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 1 publication
0
9
0
Order By: Relevance
“…Older women featured in two articles. In these, Petrusic, Todorovic, Vracevic and Jankovic (2015) highlighted the significantly hidden issue of financial abuse, and Stöckl and Penhale (2015) explored a range of different types of abuse experienced by older women, reporting on the physical and mental health issues associated with IPV. Both these articles underscore the importance of viewing IPV as a problem that does not discriminate according to age.…”
Section: Resultsmentioning
confidence: 99%
“…Older women featured in two articles. In these, Petrusic, Todorovic, Vracevic and Jankovic (2015) highlighted the significantly hidden issue of financial abuse, and Stöckl and Penhale (2015) explored a range of different types of abuse experienced by older women, reporting on the physical and mental health issues associated with IPV. Both these articles underscore the importance of viewing IPV as a problem that does not discriminate according to age.…”
Section: Resultsmentioning
confidence: 99%
“…Collectively, the identified articles addressed four broad EFFE topics. The most commonly addressed topics were (a) perception/defining of EFFE ( n = 4; Lee & Eaton, 2009; Lee et al, 2012; Lee et al, 2013; Setterlund et al, 2007), (b) risk and protective factors for victims and perpetrators ( n = 7; Bagshaw et al, 2013; Beaulieu et al, 2015; Betz‐Hamilton & Vincenti, 2018; DeLiema, 2018; Knight et al, 2016; Mukherjee, 2013; Zannettino et al, 2015), (c) impacts on family systems ( n = 2; Petrusic et al, 2015; Vincenti et al, 2014), and (d) challenges in reporting EFFE ( n = 2; Adams et al, 2014; Wendt et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…It is widely acknowledged that the definitions and conceptual development of elder abuse, including EFFE, vary across countries and cultures (Jackson, 2015; Pillemer et al, 2016). Four studies identified in this review examined the phenomenon of EFFE with an ethnic minority cultural lens (Lee & Eaton, 2009; Lee et al, 2012) or nonwestern culture lens (Lee et al, 2013; Petrusic et al, 2015). Two identified articles (Lee & Eaton, 2009; Lee et al, 2012) were guided by the theoretical construct of individualistic versus collectivistic cultural values (Markus & Kitayama, 1991), exploring Korean American elders' perceptions of EFFE.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations